Community Resilience to Militant Islamism: Who and What?: An Explorative Study of Resilience in Three Danish Communities. Issue 4 (1st October 2016) - Dalgaard-Nielsen, Anja; Schack, Patrick
ABSTRACT: Building community resilience to violent extremism increasingly figures as a goal in national security strategies and debates. The exact meaning of resilience remains unclear, complicating an informed discussion of whom and what to support. This article presents findings from an explorative study of resilience to militant Islamism in three Danish communities. It shows how families and trust-based networks, including local government, are the major sources of resilience, but also how punitive national policies and discourses work at cross purposes with resilience-building by reducing local actors' willingness and ability to share their problems, tailor solutions to local conditions, and mobilize collectively.